Preparation and fabrication of porous-Fe2O3/carbon black nanocomposite: a portable electrochemical sensor for psychotropic drug detection in environmental samples. (September 2022) - Shanmugam, R.; Ganesamurthi, J.; Chen, T.-W.; Chen, S.-M.; Balamurugan, M.; Ali, M.A.; Al-Mohaimeed, A.M.; Al-onazi, W.A.; Alagumalai, K.
Abstract: Herein, we reported the fabrication of porous iron oxide/carbon black (P–Fe2 O3 /CB) composite through a two-step engineering method. At first, Prussian blue microcubes were used as a precursor and further calcined to form P–Fe2 O3 microcubes. The intercalation of CB nanoparticles with P–Fe2 O3 nanocubes was processed through the ultrasonication method. The obtained P–Fe2 O3 /CB were successfully scrutinized through various physiochemical characterization methods. The proposed P–Fe2 O3 /CB-modified glassy carbon electrode sensor was successfully implemented in the electrochemical sensing of chlorpromazine hydrochloride due to its very low charge transfer resistance (Rct ) compared to the other electrode modifiers. The sensitive detection of CPMH through differential pulse voltammetry exemplifies an excellent electroanalytical performance such as a wide linear range of 0.5–1472 μM, a lower detection limit (0.001 μM), and an appraisable sensitivity of 1.99 μA/μM cm −2 due to its availability of a high number of active sites and its large surface area, respectively. It also expresses excellent selectivity, repeatability, reproducibility, and stability results. Moreover, the practical feasibility of the as-fabricated P–Fe2 O3 /CB/glassy carbon electrode sensor shows exquisite recovery (98.1–100.8%) results with an appraisable current response in various biological, pharmaceutical, and environmental samples. Graphical abstract: P–Fe2 O3 /CB nanocomposite-modified GCE for the electrochemical sensing of CPMH. Image 1 Highlights: Two-step engineering method for the synthesis of P–Fe2 O3 /CB nanocomposite. Intercalation between P–Fe2 O3 and CB were done via ultrasonication method. P–Fe2 O3 /CB/GCE acts as an excellent electrode modifier for the detection of CPMH. It also exemplifies excellent recoveries in various environmental sample analysis.